Hydrophobicity Enhancement of Poly (Vinylidene Fluoride-co-Hexafluoro Propylene) for Membrane Distillation - Rashid, Khalid T.; Sunarti, Abd Rahman; Alsalhy, Qusay (Universiti Kebangsaan Malaysia, 2015)
Poly (vinylidene fluoride-co-hexafluoropropylene), (PVdF-co-HFP) hollow fibre membrane was prepared by phase inversion method using different concentrations of PVP as a pore former additives in the dope solution. Surface modification was done using a formic acid through immersion technique. It was observed that the contact angle for all membranes increased due to the surfaces modification (10% of hydrophobicity increment). Based on SEM and FTIR analysis the study found that the hydrophobicity of (PVdF-co-HFP) hollow fibre membrane can be enhanced via formic acid surface modification process